Correction: The efficacy of acupuncture in relieving postoperative pain in patients with low simple anal fistula: Protocol of a prospective, randomised, controlled trial. - Min Yang; De Zheng; Xingtao Jin; Huili Tang; Weiwei Cao; Qianqian Ye; Yin Qu; Zubing Mei (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0317902.].